Teaching Music in the Reformed/Calvinist Tradition: Sphere Sovereignty and the Arts - MacInnis, John (Religions, 2017)
This article shares objectives, teaching methods, and sources of inspiration as I lead 21st-century students in engaging a Reformed/Calvinistic vision for the arts generally, and music specifically. Special explanation is made of Calvinistic concepts such as sphere sovereignty and sensus divinitatis. To conclude, I discuss aspects of a recent composition titled The God of Material Things by Jonathan Posthuma, a graduate of our college music program, whose work exemplifies many of the elements that my colleagues and I hope distinguish the accomplishments of music students beyond their education at Dordt College.